Educational Service Pricing Strategies in the Perspective of Islamic Education Marketing Management - Amarullah, Mohammad Syarifuddin; Farisi, Ahmad Nu'man; Zohriah, Anis; Djabidi, Faizal (International Journal of Business and Applied Economics, 2025)
Determining the price of educational services is one of the strategic elements in education marketing management, especially in Islamic educational institutions that have a dual mission: to produce people with Islamic character while ensuring the sustainability of the institution. This article explores the fundamentals of education service pricing strategies, pricing strategy objectives, and relevant techniques. With a descriptive-qualitative approach, this study aims to provide practical and academic insights for managers of Islamic educational institutions in managing the price aspect as a strategic marketing instrument.